2020
DOI: 10.1186/s40550-020-00079-2
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of mycotoxins and occurrence of aflatoxins in poultry feeds and feed ingredients in selected regions of Uganda

Abstract: Background: Aflatoxins are a category of mycotoxins produced by certain molds naturally occurring as food and feed contaminants with toxic effects to both animals and humans. In Uganda, previous studies on aflatoxins mainly considered human foods, but scarce information exists for animal feeds. The study aimed at establishing the current status of aflatoxins contamination of poultry feeds, level of awareness and the existing technological challenges and innovations to mycotoxin control in Uganda. Method: Mycot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 28 publications
1
27
0
3
Order By: Relevance
“…(2018) found that aflatoxin awareness was deficient among uneducated and socially unexposed farmers in Tanzania. Similar low awareness levels are reported from Ethiopia and Uganda (Guchi, 2015; Nakavuma et al., 2020). Studies in Vietnam and Nigeria also reported similar low aflatoxin‐related awareness among consumers (Adekoya et al., 2017; Lee et al., 2017).…”
Section: Current Aflatoxin‐contamination Prevention Methodssupporting
confidence: 79%
“…(2018) found that aflatoxin awareness was deficient among uneducated and socially unexposed farmers in Tanzania. Similar low awareness levels are reported from Ethiopia and Uganda (Guchi, 2015; Nakavuma et al., 2020). Studies in Vietnam and Nigeria also reported similar low aflatoxin‐related awareness among consumers (Adekoya et al., 2017; Lee et al., 2017).…”
Section: Current Aflatoxin‐contamination Prevention Methodssupporting
confidence: 79%
“…Eighteen 25 g aliquots were randomly assigned to a 2 × 3 factorial arrangement i.e., 9 aliquots for each of the two milling methods and three aliquots randomly selected for spiking to achieve three levels of AFB1 (0, 20 or 100 ppb). The EU legal AFB1 residue limits in feed for adult poultry and young animals are 20 and 10 ppb respectively (EU, 2002), but in tropical countries it is common to find feed naturally contaminated with 100 ppb AFB1 and above [ 13 , 15 , 18 , 19 ]. Of the 9 aliquots assigned to each group, 3 sets each of 3 aliquots were randomly selected for either of the three AFB1 levels.…”
Section: Methodsmentioning
confidence: 99%
“…Levels of 36 ppb (mean) aflatoxin B1 was observed in Sudan [ 12 ], 100 ppb (mean) in India [ 13 ], 10–166 ppb aflatoxin in Pakistan [ 14 ], 74 ppb (mean) in Nigeria [ 15 ], 2.7 ppb (median) in Argentina [ 16 ] and 20–50 ppb in Kenya [ 17 ]. Recently, aflatoxin levels of 7.5–393.5 ppb in feed processing plants samples and 19.0–188.5 ppb in samples collected from farmers in Uganda [ 18 ] and 0.2–318 ppb in 2020 in Kenya were reported [ 19 ]. Maximum allowable limits for aflatoxin content in human food and animal feed have been established in more than 100 countries [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a previous study in Uganda revealed poultry feed contamination with aflatoxins at levels between 7.5 ± 0.71 and 393. 5 ± 19.09 µg/kg; with only 17.9% passing the FDA limits [10]. Unfortunately, there is limited monitoring and enforcement of the regulations for management of mycotoxin contamination in the animal feed industry in Uganda.…”
Section: Introductionmentioning
confidence: 99%